1997
DOI: 10.1046/j.1365-2982.1997.d01-58.x
|View full text |Cite
|
Sign up to set email alerts
|

Central regulation of gastric emptying of solid nutrient meals by corticotropin releasing factor

Abstract: Central regulation of gastric emptying of a solid nutrient meal and spatial and temporal parameters of gastro-pyloro-duodenal contractions by corticotropin-releasing factor (CRF) were investigated in conscious dogs. Intracerebroventricular (i.c.v.) infusion of CRF at 0.033 nmol kg-1 min-1 for 15 min in a volume of 0.2 mL significantly delayed the total gastric emptying time of the meal. I.c.v infusion of CRF also increased the mean frequency of proximal duodenal contractions and decreased the percentage of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…In those experiments, injection of CRF or Ucn 1 induced an increase in the contractile activity of the duodenum but inhibited the percentage of propagated duodenal contractions (21,23). These effects of CRF or Ucn 1 on the duodenal contractile activity are in agreement with the present results, in which CRF or Ucn 1 elicited an increase of the duodenal smooth muscle contractions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In those experiments, injection of CRF or Ucn 1 induced an increase in the contractile activity of the duodenum but inhibited the percentage of propagated duodenal contractions (21,23). These effects of CRF or Ucn 1 on the duodenal contractile activity are in agreement with the present results, in which CRF or Ucn 1 elicited an increase of the duodenal smooth muscle contractions.…”
Section: Discussionsupporting
confidence: 82%
“…Functional experiments showed that, in vivo, central or peripheral administration of CRF or Ucn 1 inhibited gastric emptying, delayed small intestinal transit, and stimulated colonic transit (21,23,31,57,58). In those experiments, injection of CRF or Ucn 1 induced an increase in the contractile activity of the duodenum but inhibited the percentage of propagated duodenal contractions (21,23).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the pituitary gland or adrenal glands had no effect on CRF inhibition of gastric emptying; this indicates that the gastric effect is not secondary to the activation of the HPA axis (61,62). All reports, except 2 (61, 63), have identified the vagus nerve as the main pathway mediating the delayed gastric transit and inhibition of gastric motility induced by central injection of either CRF or urocortin 1 in rats and dogs (54,55,57,59,62,64,65). By contrast, the delayed gastric emptying induced by injection of urocortin 2 into the CSF is not altered by gastric vagotomy and instead requires the integrity of the sympathetic nervous system and peripheral α-adrenergic receptors (57).…”
Section: Link Between Crf Receptors In the Brain And Stressrelated Almentioning
confidence: 99%
“…CRF, urocortin 1, urocortin 2, and the nonmammalian CRF-related peptides sauvagine and urotensin I inhibit gastric emptying of noncaloric liquid, caloric liquid, and solid food when injected into the cerebrospinal fluid (CSF) of several nonprimate mammals (53). These peptides also inhibit basal and cholinergic-stimulated gastric motility in rodents and dogs (54,55). CRF 2 is the CRF receptor subtype in the brain through which CRF and urocortins injected into the CSF primarily initiate their inhibitory effect on gastric transit and motility (56)(57)(58).…”
Section: Link Between Crf Receptors In the Brain And Stressrelated Almentioning
confidence: 99%
“…One physiological effect of stress is the inhibition of digestive function, a mechanism that allows animals to divert blood flow and energy reserves to organs essential for dealing with the stressor. Stress-induced alterations to digestive physiology that have garnered the most empirical attention include inhibition of gastrointestinal motility (Coskun et al 1997;Lee & Sarna 1997;Plourde 1999;Taché et al 1999) and the acceleration of colonic transit (Mönnikes et al 1993). These effects are mediated by corticotropin-releasing factor (CRF), a neuropeptide at the apex of the neuroendocrine stress axis (Mö nnikes et al 1993;Taché et al 1999).…”
Section: Introductionmentioning
confidence: 99%